Amyloid Imaging, Cerebrospinal Fluid Biomarkers Predict Driving Performance Among Cognitively Normal Individuals. (January 2017) - Roe, Catherine M.; Barco, Peggy P.; Head, Denise M.; Ghoshal, Nupur; Selsor, Natalie; Babulal, Ganesh M.; Fierberg, Rebecca; Vernon, Elizabeth K.; Shulman, Neal; Johnson, Ann; Fague, Scot; Xiong, Chengjie; et al.
Abstract : Postmortem brain studies of older drivers killed in car accidents indicate that many had Alzheimer disease (AD) neuropathologic changes. We examined whether AD biomarkers are related to driving performance among cognitively normal older adults. Individuals with normal cognition, aged 65+ years, and driving at least once per week, were recruited. Participants (N=129) took part in clinical assessments, a driving test, and positron emission tomography imaging with Pittsburgh compound B (PIB) and/or cerebrospinal fluid (CSF) collection. General linear models tested whether the number of driving errors differed as a function of each of the biomarker variables (mean cortical binding potential for PIB, and CSF Aβ42, tau, ptau181, tau/Aβ42, ptau181 /Aβ42 ). Higher ratios of CSF tau/Aβ42, ptau181 /Aβ42, and PIB mean cortical binding potential, were associated with more driving errors ( P <0.05). Preclinical AD may have subtle cognitive and functional effects, which alone may go unnoticed. However, when combined, these changes may impact complex behaviors such as driving.